Evaluating the Impact of Tax Incentives on Small and Medium Enterprises (SMEs): Policy Effectiveness and Compliance Behavior - Pegi Sugiartini (Sekolah Tinggi Agama Islam Kuningan, 2025)
Tax incentives have been widely used to promote small and medium enterprises' (SMEs) growth. However, little is known about the impact of tax incentives on SMEs. This study aims to provide a nuanced understanding of how tax incentives affect SMEs' compliance behavior in response to tax incentives. The study uses a mixed-methods approach, combining both qualitative and quantitative data, to assess the effectiveness of tax incentive policies on the growth and compliance behavior of SMEs in Indonesia. The data collected from 300 SMEs across manufacturing, retail, and service sectors in Indonesia show that tax incentives can be effective tools for fostering SME growth and improving compliance, provided they are easily understandable and accessible. The research demonstrates that SMEs aware of and utilizing tax incentives show higher compliance rates and greater investment growth, particularly in capital-intensive sectors like manufacturing. This research contributes to the existing body of literature by suggesting that accessibility and clarity of information are as crucial as financial incentives in influencing compliance behavior. In addition, the research will serve as a reference for tax authorities in developing countries seeking to create more efficient and SME-friendly tax regimes.